A Quantitative Descriptive Study on the Flourishing Level of Elementary School Teachers: A Psychological Approach in Education - I Dewa Ayu Eka Purba Dharma Tari; I Gede Ratnaya; I Gusti Ngurah Pujawan; I Made Candiasa (Buletin Edukasi Indonesia, 2025)
This study aims to understand the level of psychological well-being (flourishing) of teachers in primary schools. For this purpose, the research method was a psychological assessment using the PERMA model, which includes Positive Emotion, Engagement, Relationships, Meaning and Accomplishment. This study used a descriptive quantitative approach and involved 33 teachers who had a minimum of two years of teaching experience. The data were collected through the PERMA Profiler instrument which has been translated into Bahasa Indonesia. The data were analysed using SPSS software in a descriptive manner. he results of this study revealed that the majority of teachers were in the flourished category, with high percentages in the dimensions of Positive Emotions (96.7%), Relationships (96.7%), Engagement (84.84%), Meaning (84.84%), and Achievement (84.84%). However, around 24.24% of teachers belong to the not flourished group, especially in the dimensions of Engagement and Meaning. These findings suggest that although teachers' psychological well-being is generally satisfactory, there are some areas that need improvement. The psychological assessment approach using the PERMA model provides a complete insight into the mental state of teachers and can be used as a basis for making education policies more humane and sustainable.